The effectiveness of peer tutoring to teach reading: viewed from students’ self-esteem - Arina Chusnatayaini; Eka Wulandari (Jurnal Linguistik Terapan, 2013)
This research aims at finding out whether: (1) Peer Tutoring technique is more effective than Direct Instruction in teaching reading to the second semester students of English department of UNISKA in the Academic Year of 2011/2012; (2) the second semester students of English department of UNISKA who have high self-esteem have better reading skill than those having low self-esteem; and (3) there is interaction between teaching techniques and students’ self-esteem in teaching reading. The method which was applied in this research was an experimental study. The research was conducted at UNISKA Kediri in the academic year of 2011/2012. The population of the research was the second semester students of UNISKA Kediri. Two samples were taken by using cluster random sampling technique. Class B1 was used as the experimental class and class B2 as the control class. Each class consists of 22 students. The steps for the research were: (1) distributing self-esteem questionnaire to know students’ self-esteem; (2) applying teaching techniques to the students; (3) distributing post test; and (4) analyzing the students’ reading ability. The data were obtained from self-esteem questionnaire and reading test. Furthermore, to analyze the data, the researcher applied descriptive and inferential statistics using ANOVA and Tukey’s test. The result of the study leads to the conclusions that: (1) Peer Tutoring is more effective than Direct Instruction to teach reading for the second semester students of UNISKA Kediri in the Academic Year of 2011/2012; (2) The students who have high self-esteem have better reading ability than those who have low self-esteem; and (3) There is an interaction between teaching techniques and students’ self-esteem to teach reading at the second semester students of UNISKA Kediri. Finally, the results of this research imply that Peer Tutoring is more effective than Direct Instruction to teach reading.